Production latencies of morphologically simple and complex verbs in aphasia - Faroqi-Shah, Yasmeen (2010)
There are several accounts of why some individuals with post-stroke aphasia experience difficulty in producing morphologically complex verbs. Although a majority of these individuals also produce syntactically flawed utterances, at least two accounts focus on word-level encoding operations. One account proposes a difficulty with rule-governed affixation, predicting that verbs without affixes (stems and irregular past) should be produced with ease. The second account emphasises the contribution of phonological encoding, noting that morphological complexity is often confounded by phonological complexity. The present study investigated the effect of morphological complexity (presence vs. absence of affixes) on verb production when phonological complexity and lexical frequency was controlled. A novel delayed repetition paradigm was used, accuracy and latency of production were the dependent measures. Data from nine agrammatic aphasic and nine unimpaired participants revealed no effects of morphological complexity, but a significant effect of frequency on production latency. The results indicate that morphological complexity plays little role, if any, in production difficulty, at least for this experimental task and this group of non-apraxic agrammatic aphasic individuals. A difficulty in usage of contextually appropriate verb inflections, rather than in morphophonological encoding, is suggested.